Gender-Sensitive Remittances and Asset Building in the Philippines - Ang, Alvin P (Archīum Ateneo, 2015)
This publication aims to add to the remittances for development discourse, as an input into policy, programme and services development. It offers information and sex-disaggregated data on remittance flows, patterns, recognizing the differences between women and men as senders and recipients of remittances. The study considers how these gender dimensions intersect with specific social and economic contexts so that programmes are responsive to the needs at different levels – local, national, international, as appropriate and in a collaborative manner among key stakeholders. The study recommends emphasis on the meaningful participation of women migrant workers in decision-making processes on remittance-oriented initiatives, not merely as remittances senders and investors but beneficiaries and protagonists of development